2017
DOI: 10.3389/fnana.2017.00015
|View full text |Cite
|
Sign up to set email alerts
|

The Brainstem in Emotion: A Review

Abstract: Emotions depend upon the integrated activity of neural networks that modulate arousal, autonomic function, motor control, and somatosensation. Brainstem nodes play critical roles in each of these networks, but prior studies of the neuroanatomic basis of emotion, particularly in the human neuropsychological literature, have mostly focused on the contributions of cortical rather than subcortical structures. Given the size and complexity of brainstem circuits, elucidating their structural and functional propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
134
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(154 citation statements)
references
References 102 publications
4
134
0
4
Order By: Relevance
“…people with better interoceptive accuracy showed greater retention of the physiological fear response at the end of the therapy. This suggests a connection; perhaps through descending 'predictive' influences of enhanced interoceptive ability on midbrain monoamine nuclei, influencing both perceptual precision and efferent sympathetic outflow (53).…”
Section: Discussionmentioning
confidence: 99%
“…people with better interoceptive accuracy showed greater retention of the physiological fear response at the end of the therapy. This suggests a connection; perhaps through descending 'predictive' influences of enhanced interoceptive ability on midbrain monoamine nuclei, influencing both perceptual precision and efferent sympathetic outflow (53).…”
Section: Discussionmentioning
confidence: 99%
“…It also plays a pivotal role in sensory information processing, in eliciting goal-oriented behavior, in the regulation of social attention, and in the modulation of emotions (Berntson & Micco, 1976;Geva et al, 2017;Venkatraman, Edlow, & Immordino-Yang, 2017). Structural MRI studies of ASD individuals have demonstrated the potential role of the brainstem in the pathophysiology of ASD (Gaffney, Kuperman, Tsai, & Minchin, 1988) (Jou et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation for the strong midbrain finding is that the midbrain is the starting point of the dopamine and serotonin pathways, which then project to wide areas of the brain including innervations to the dmPFC and the TPJ (32). Whereas the ventral tegmental area (VTA) is the source of the mesocorticolimbic dopamine pathway, the raphe nuclei are clustered along the midline throughout the brainstem, constituting the source of serotoninergic innervation (33). According to Abu-Akel (34), the integrity of the dopaminergic and serotoninergic systems is the neurochemical basis that sustains ToM ability and abnormalities in this system can account for ToM impairments.…”
Section: Discussionmentioning
confidence: 99%